RANCANG BANGUN SIMULATOR BEBAN 3 FASA BERBASIS PROGRAMMABLE LOGIC CONTROLLER (PLC) OMRON CP1E - Andi Wawan Indrawan; Agussalim; Wisna saputri Alfira WS; Darmawansyah Bandoe; Syachru Ramadhany; Muhammad Asril Gunawan, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The aim of this research is to design a 3-phase load simulator consisting of resistive, inductive, and capacitive loads with a maximum load capacity of 2 Ampere with adjustable load variations. This simulator is used in testing reactive power compensation at the Power Systems Laboratory in the Department of Electrical Engineering, Ujung Pandang State Polytechnic. Loading is done manually to see the effect of each increase or change in load on the power factor, voltage and current on the receiving and sending sides. The controller for managing load changes uses an Omron Type CP1E PLC. The PLC receives commands via a push button to determine which load is fed to the electrical network, while to read electrical quantities the Larkin 3 phase LCD LR-3D3Y is used. As a result of this design, the panel created can simulate resistive loads with 8 load circuit configurations with a maximum value of 1.9 A. Meanwhile, the inductive load circuit configuration produces a maximum current value in the eighth step of 2.19 A with a pf of 0.11. The capacitive load produces a current value of 2.2A and a pf of 0.12 with several loading step variations of 6 steps